A three-dimensional UTD heuristic diffraction coefficient for complex penetrable wedges. - Bernardi, P. (IEEE Transactions on antennas and propagation)
A three-dimensional heuristic diffraction coefficient, useful to predict the electromagnetic field scattered from penetrable wedges of complex geometry, is presented. The model, based on a modification of the exact uniform theory of diffraction (UTD) metallic wedge diffraction coefficient, allows the analysis of a large class of penetrable objects with an adequate degree of accuracy. Numerical results concerning the scattering from solid and hollow penetrable wedges show the suitability of the proposed diffraction coefficient to analyze complex structures of large practical interest. A good agreement with exact numerical results already available in the literature has been found